Screening of medium constituents for the cultivation of Scenedesmus dimorphus UTEX 1237 using 2k factorial design approach - Ravindran, Bavistra; Kassim, Mohd Asyraf; Mohamed, Mohd Shamzi (Institute of Physics Publishing, 2020)
Freshwater microalga, Scenedesmus dimorphus is a beneficial natural resource for producing biofuel and novel bioproducts. S. dimorphus growth greatly depends on physical culture conditions as well as medium constituents. A study was conducted to select the suitable medium components that could promote high biomass production in S. dimorphus UTEX 1237. Screening of growth medium constituents was performed using the two-level factorial design (2k FD) method. S. dimorphus was cultivated in TAPS aquaculture medium employing two types of carbon source (sodium bicarbonate and acetic acid) and three types of nitrogen sources (ammonium chloride, sodium nitrate, and urea). Consequently, medium components that significantly influenced biomass production comprised of acetic acid, ammonium chloride, and urea. Two weeks of S. dimorphus cultivation in shake flask system consisting of 1.5 g/L of acetic acid, 10 g/L of ammonium chloride and 0.4 g/L of urea was found to affect a specific growth rate of 0.0049 h−1 and biomass productivity of 0.05 g/L/day, thus affecting 66.7% improvement over normal TAP formulation.